TRANSFORMATISASI LITURGI MELALUI NYANYIAN LITURGI INKULTURATIF - didimus, satrio (Pastoralia Jurnal Penelitian Dosen, 2024)
Inculturative liturgy through inculturative liturgical songs is a reality in the Catholic Church which illustrates the universality of the Catholic Church with the world and its dynamics. The aim of this research is to improve the people's understanding of liturgy, inculturative liturgy through inculturative liturgical songs which have an impact on selecting liturgical songs correctly and appropriately, as well as revising the overall implementation of the liturgy so that it is in accordance with the general rules of inculturative liturgy determined by Catholic Church. The method the author uses is a qualitative research method with a descriptive approach. This method was used with the aim that researchers were able to find clear answers to the main problems found. Researchers collected data using three techniques: interviews, observation and documentation. Through interviews, the researcher asks logical questions, through observation, the researcher sees and records events that the author personally witnessed and through documentation, the researcher collects evidence in the form of photos and recordings and records previous events. Next, the researcher carried out data reduction by selecting data that had the same character and was important, presenting the data using descriptive-narrative and data verification to produce conclusions. The results that the author obtained are the reality that people do not understand liturgy, inculturative liturgy through inculturative songs and this has an impact on the choice of liturgical songs which are dominated by regional songs. The conclusion is in the form of a logical and systematic presentation of the entire research describing the problems found, a summary of the content and discussion.